Subpopulations of mononuclear cells in ageing: expansion of the null cell compartment and decrease in the number of T and B cells in human blood. - Ligthart, G J (1985)
Study of the immune system in ageing has yielded conflicting results. These controversies are mainly due to the selection of the subjects studied. We investigated the mononuclear cell subpopulations in the peripheral blood of subjects fulfilling strict admission criteria meant to exclude persons with diseases that influence the immune system. These criteria are described in the SENIEUR protocol devised by a working group in the framework of EURAGE, the Concerted Action Programme on Ageing of the European Community. We compared two groups of volunteers aged 25-34 years, and 75-84 years. Mononuclear cells were investigated by two-wavelength immunofluorescence combined with phase-contrast microscopy. We found a striking increase in the number of 'null' cells (non-T, non-B, non-monocyte) in the blood of the aged persons. The number of T cells was decreased, especially in the suppressor/cytotoxic subset. The number of B cells was slightly, but significantly, decreased; the number of monocytes did not change. The changes in these cell populations may be related to functional changes, and their quantification could be used to monitor attempts to reconstitute the immune defects in ageing. These findings can also serve as reference values in the study of aged persons not fulfilling the SENIEUR criteria, which, in turn, can contribute to the dissection of the influence of disease versus age on the immune system.